2006
DOI: 10.4049/jimmunol.177.7.4247
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: IL-7-Independent Regulation of IL-7 Receptor α Expression and Memory CD8 T Cell Development

Abstract: Expression of IL-7Rα on a subset of Ag-specific effector CD8 T cells is believed to identify memory cell precursors. However, whether IL-7 regulates IL-7Rα expression in vivo and is responsible for selective survival of IL-7Rα+ effector cells is unknown. Our results show that in the absence of IL-7, IL-7Rα expression was extinguished on the majority of CD8 T cells responding to virus infection, sustained on a subset of effector cells transitioning to memory, and expressed at high levels by memory cells. Additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
54
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 31 publications
4
54
1
Order By: Relevance
“…This point is made most clearly by our data, because the effector cells destined for death (that express KLRG1) could actually be distinguished, and these cells were not saved by the IL-7R␣tg. Our work here also supports and greatly extends two recent studies that suggested IL-7 signals alone do not instruct activated CD8 T cells to express IL-7R␣ or to become memory CD8 T cells (13,26).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This point is made most clearly by our data, because the effector cells destined for death (that express KLRG1) could actually be distinguished, and these cells were not saved by the IL-7R␣tg. Our work here also supports and greatly extends two recent studies that suggested IL-7 signals alone do not instruct activated CD8 T cells to express IL-7R␣ or to become memory CD8 T cells (13,26).…”
Section: Discussionsupporting
confidence: 77%
“…Signals emanating from the cytokine receptor for IL-7 are particularly critical for the generation and long-term maintenance of memory CD8 T cells (7-10). Naïve CD8 T cells express IL-7 receptor ␣-chain (IL-7R␣), but during acute viral and bacterial infection, as activated CD8 T cells expand, most down-regulate IL-7R␣ (referred to as IL-7R␣ lo ) (7,8,(11)(12)(13)(14). The small subset of effector cells that expresses IL-7R␣ (referred to as IL-7R␣ hi ) preferentially survives and matures into memory CD8 T cells that express increased amounts of CD27, Bcl-2, and IL-2 and undergo IL-15-driven homeostatic turnover (7,(10)(11)(12)15).…”
mentioning
confidence: 99%
“…In both the high and low precursor frequency transfers, IL-7R expression was down-regulated by most cells by day 3 after infection ( compared with day 3. By day 10, all remaining cells expressed levels of IL-7R that were increased over that of naïve TEa cells, as has been previously shown for cells transiting to memory CD8 T cell development (14,32,33). Therefore, regulation of IL-7R expression was not linked to initial precursor frequency and did not correlate with memory cell development.…”
Section: Resultsmentioning
confidence: 49%
“…These differences may have a considerable importance at biological level. Interestingly, a recent paper by Lefrancois and colleagues has demonstrated that both IL-7R␣ regulation and CD8 T cell memory formation occurs in IL-7-independent manner (35). We do not exclude the possibility that sustained IL-7R␣ expression in activated T cells confers a competitive advantage to other homeostatic factors, such as thymic stromal lymphopoietin (TSLP).…”
Section: Discussionmentioning
confidence: 99%